Factors Affecting Employee Loyalty at PT. Permodalan Nasional Madani Tangerang Branch - Eva Novita Sari; Agus Salim (Dinasti International Journal of Education Management And Social Science, 2023)
This study aims to analyze the effect of service quality provided, the effect of service quality on employee satisfaction, the effect of service quality on employee loyalty mediated by employee satisfaction and the effect of employee satisfaction on employee loyalty at PT. Permodalan Nasional Madani Tangerang Branch. With the number of samples in this study 125 respondents. From the results of the analysis that has been carried out, the results show that service quality has a positive effect on employee loyalty with an original sample estimate (O) value of 0.348, service quality has a positive effect on employee satisfaction with an original sample estimate (O) value of 0.825, employee satisfaction has a positive effect on loyalty employee original sample estimate (O) value of 0.506, and service quality has a positive effect on employee loyalty mediated by employee satisfaction showing an original sample estimate (O) value of 0.417 so that the four hypotheses can be accepted.